Endothelium-Released Microvesicles Transport miR-126 That Induces Proangiogenic Reprogramming in Monocytes - Arderiu, Gemma; Peña, Esther; Civit-Urgell, Anna; Badimon, Lina (Frontiers in Immunology, 2022)
We have recently shown that in ischemic tissue the hypoxic endothelial cells (EC) release extracellular microvesicles (EMVs) that are rich in tissue factor (TF). These TF-EMVs induce monocyte (Mo) homing to the ischemic zone, their differentiation into EC-like cells and the formation of new blood vessels increasing tissue perfusion. In addition to membrane proteins, EMVs contain non-coding RNAs that can modulate cellular signaling pathways in the recipient cells. Here, we have investigated whether miRNA contained into secreted EMVs may be transferred into Mo where they could modulate EC-like cell differentiation and angiogenic responses. Our results indicated that EMVs released from activated ECs contain high levels of miR-126 and that the levels are directly proportional to TF expression in EMVs. Interestingly, miR-126 is transferred to Mo when they are incubated with TF-EMVs. Increased levels of miR-126 in Mo do not promote EC-like cell differentiation but regulate angiogenesis by targeting several components of the VEGF pathway, as SPRED1 and PI3KR2. Our findings reveal that activated ECs secrete EMVs carrying miR-126, that can modulate Mo reprogramming of angiogenic genes.